A First World War example of forensic archaeology - Martin, Victoria (Elsevier, 2020)
Between 1919 and 1921, the First World War battlefields of France and Belgium were searched by the British Army for the single graves and small cemeteries containing the bodies of British and Commonwealth soldiers. This process was called “concentration”. When found, these graves were exhumed, the bodies within were examined to try and establish or confirm identification, and were subsequently reburied in newly built. Imperial War Grave Commission cemeteries. This task was carried out by military staff working for the Directorate of Graves Registration and Enquiries. They had no forensic or medical experience and yet in less than three years they moved hundreds of thousands of graves, on a scale never seen before or since. Written records were issued for the soldiers working on exhumation in 1919 giving detailed instructions on how to search for buried or unburied individuals, the method to follow for excavating these graves and directions for the examination of bodies. These instructions are very similar to those used in modern forensic archaeology when excavating single or mass graves, or when dealing with multiple bodies following mass disasters. They show an awareness of the effects of human burials on the surrounding environment and address search and excavation problems that are still experienced. The example given here in France and Belgium is one of the earliest examples of Forensic Archaeology for humanitarian purposes, and the instructions issued are probably the earliest written instructions for a Forensic Archaeological excavation.
Keywords: Ground search; Forensic archaeology; Grave concentration; Exhumation; First World War